Desain dan Implementasi Sistem Penyiraman Otomatis Berbasis IoT Menggunakan Mikrokontroler ESP - Diyajeng Luluk Karlina (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This research develops a prototype of an automatic watering device based on the Internet of Things (IoT) and a soil moisture sensor to improve the efficiency of watering crops in agricultural fields. The main problem addressed is the consistency and efficiency of watering in large agricultural fields, where traditional management is prone to human error and inefficient water use. The developed prototype uses an ESP8266 microcontroller (NodeMCU) as the brain of the system connected to a Wi-Fi network, allowing remote monitoring and control via the Blynk application. A soil moisture sensor is used to detect soil conditions in real-time, triggering watering only when needed. This helps optimize water use and increase agricultural productivity sustainably. This research outlines the methodological steps from design, manufacturing, to implementation of the prototype in the field. Evaluation of the results shows that the system successfully regulates watering effectively based on soil conditions, with positive responses from farmers as end users.